E-041 Use of Flow Diverters in the Endovascular Reconstruction of Fusiform Dissecting Vertebral Artery Aneurysms. (26th July 2014) - Puri, A; Massari, F; Hou, S; Perras, M; Brooks, C; Stout, C; Gounis, M; Wakhloo, A
Abstract : Introduction/purpose: Fusiform aneurysms (FUANs) of vertebral artery are difficult to treat by using current surgical techniques. Endovascular techniques like parent vessel occlusion, trapping, coiling, stent assisted coiling or stent mono-therapy is currently used to treat these aneurysms. The purpose of this study is to assess the efficacy and safety of flow diverters (Pipeline Embolization Device) in the treatment of vertebral artery FUANs compared to currently used therapeutic modalities. Materials and methods: From July 2012 to October 2013, a total of 5 vertebral artery fusiform dissecting aneurysms in 5 patients (2 men and 3 women; age range, 39–59 years; mean age, 50.8 years) were treated with pipeline embolization device (PED) at our institution. In 2 patients the aneurysms were an incidental finding whereas in the other 3 cases were associated to neurologic symptoms, such as visual changes, ataxia, facial numbness or vertigo. Location of the aneurysms was as follows: 4 aneurysms on the right and 1 on the left side. 4 aneurysms were centerd at the V4 segment of the vertebral artery (intradural); only one was located at the vertebral V3-V4 segments junction (intra/extradural). Only one patient had family history indicative for intracranial aneurysm. Aneurysms ranged from 5 to 13 mm in maximal diameter. The technical feasibility of the procedure, procedure-related complications, angiographic results, and clinical outcome were evaluated. Results: In every case, endovascular treatment was achieved. Immediate angiography demonstrated intra-aneurysmal contrast stagnation, with parent artery preservation in all cases. Major procedure-related complications were not observed. A brief temporary episode of dysarthria was noted in one of the patient. None of the treated aneurysms experienced bleeding or thrombo-embolic complication during the follow-up time. At 6 month follow-up (4 patients) was noted a complete/near complete aneurysm obliteration in 3 patients and partial obliteration in 1 patient. At 1 year follow-up (2 patients) was noted a progression to complete aneurysm obliteration in 1 patient and stable partial embolization in 1 patient. No intimal hyperplasia was noted at 6–12 months follow-up in the cohort of patients analyzed. Conclusion: In our preliminary experience vertebral artery fusiform dissecting aneurysms treatment with PED is a safe and efficacious option in treating dissecting or fusiform intracranial aneurysms. Long term studies and larger cohort is recommended for further evaluation of this treatment strategy. Disclosures: A. Puri: None. F. Massari: None. S. Hou: None. M. Perras: None. C. Brooks: None. C. Stout: None. M. Gounis: None. A. Wakhloo: None.